Examen especial a las cuentas de ingresos, gastos y cumplimiento tributario de la avícola Reina del Cisne-Cisnavi, de la ciudad de Riobamba, período 2016. - Guaño Bonilla, Tania Maribel (2018)
In the present research work, a Special Examination was made to the Income, Expenses and Tax Compliance accounts of the "Reina del Cisne-Cisnavi" Poultry of the City of Riobamba, Period 2016, which is structured as follows: First of all, we have the Introduction, Justification, General and specific objectives; Next, the Theoretical Framework is presented, the conceptual part of the research was described, which is made up of the Generalities of the company, Theoretical Foundation in it is defined to the Audit, Income, Expenses, Tax Obligation, Special Examination, its classification, and the phases that intervened in this process. Mention is made of the Methodology, in which the inductive and analytical method was used to analyze and review the documentation in an orderly manner, the appropriate use of a design helped to establish descriptively the reality of the facts. In the process of results and discussion, there is the Internal Control Evaluation of the Income, Expenses and Tax Compliance accounts, and the development of each of the procedures of the special examination programs. In the conclusions and recommendations, the findings found during the special examination process are developed, which are focused on the main people responsible for the administration of the "Reina del Cisne- Cisnavi" Poultry. Finally, there is the bibliography and the annexes, in which the working papers with the development of the Special Exam are recorded.